Aqueous wetting dispersant and method for its preparation
Patent Information
- Application Number
- CN202610728806.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-26
- Publication Date
- 2026-09-08
- Estimated Expiration
- 2046-05-26
AI Technical Summary
然而,现有的分散剂功能相对单一,涂料中需要添加的助剂种类较多,易影响涂料性能
[0012] The beneficial effects of this invention are as follows: The aqueous wetting and dispersing agent provided by this invention is composed of a star polymer, functional carbon dots, and a synergist, integrating dispersion, wetting, and antibacterial properties. The star polymer is the main material, and its multi-arm branched topology provides more anchoring points and hydrophilic arms, achieving efficient dispersion and rapid wetting of pigments and fillers. The functional carbon dots contain chitosan and are deposited with silver nanoparticles to provide continuous contact antibacterial properties. The carbon dots themselves generate singlet oxygen under light to achieve photodynamic antibacterial effects, with an antibacterial rate of up to 95% under light. The synergist is montmorillonite modified with organic polymer-linked superlayers. Its layered structure and polymer chains can effectively load carbon dots and trap star polymers, thereby achieving a strong bond in the composite material. Furthermore, it is rich in zwitterions and can form electrostatic attraction with the carboxyl groups and phosphate groups of the star polymer and hydrogen bonding with the carbon dots, thereby enhancing the stability of the composite structure.
Smart Images

Figure CN122255780B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating additives technology, specifically to an aqueous wetting and dispersing agent and its preparation method. Background Technology
[0002] Paint is a viscous liquid applied to the surface of an object to be protected or decorated, forming a firmly adhering, continuous film. It is typically based on resin, oil, or emulsion, with or without pigments and fillers, and with appropriate additives, prepared using organic solvents or water. Additives are classified into many types according to their function, such as defoamers, leveling agents, dispersants, wetting agents, and antioxidants. They are generally added in small amounts but play a significant role. Dispersants are surfactants that possess both lipophilic and hydrophilic properties within their molecules. For paints with added pigments and fillers, some solid or liquid particles of organic and inorganic pigments are difficult to dissolve in the paint system. Adding dispersants promotes uniform dispersion and prevents particle sedimentation and aggregation. However, existing dispersants have relatively limited functions, and the need for multiple types of additives in paints can easily affect paint performance. Composite dispersants lack synergy among their multiple components, making it difficult to achieve multiple beneficial effects while maintaining low addition levels. They are also prone to precipitation in high-solids systems or during long-term storage, leading to pigment and filler agglomeration or sedimentation and affecting coating quality. Summary of the Invention
[0003] To address the shortcomings of existing technologies, this invention provides a multi-component synergistic wetting and dispersing agent.
[0004] To achieve the above objectives, the present invention provides the following technical solution: An aqueous wetting and dispersing agent comprises: a star-shaped polymer, functional carbon dots, a synergist, and deionized water; wherein, The star polymer was prepared by using pentaerythritol as a starting agent to prepare a six-arm initiator, and using MAA, HEMAP and PEGMA as comonomers, and polymerized under ATRP initiation conditions. The functional carbon dots are obtained by preparing carbon dots through a hydrothermal reaction using citric acid, chitosan, and L-cysteine as raw materials, followed by the reduction of silver ammonia to deposit silver ions on the surface of the carbon dots. The synergistic agent is modified montmorillonite, which is obtained by intercalation modification of organomontmorillonite with acryloyloxyethyltrimethylammonium chloride and then polymerization reaction with acrylamide and 2-acrylamidododecylsulfonic acid.
[0005] Furthermore, the weight parts of each raw material are: 25-40 parts of star-shaped polymer, 1-5 parts of functional carbon dots, 2-8 parts of synergistic agent, and 60 parts of deionized water.
[0006] Furthermore, the preparation process of the star-shaped polymer is as follows: S1. Dissolve dipentaerythritol and triethylamine in dichloromethane, place in an ice-water bath, and slowly add a dichloromethane solution of α-bromoisobutyryl bromide while stirring. After the addition is complete, remove the ice bath and stir at room temperature for 24-48 h. Filter, wash the filtrate successively with dilute hydrochloric acid (HCl), saturated NaHCO3, and saturated brine, dry with anhydrous MgSO4, filter again, evaporate to dryness, and recrystallize from ethyl acetate / n-hexane to obtain a white solid, which is the six-armed initiator. S2. Add a six-arm initiator, NaBr, Mesohemin-(MPEG)2 (iron porphyrin catalyst), and monomers MAA (methacrylic acid) and HEMAP (hydroxyethyl methacrylate phosphate) to a dry reaction flask. Add water and DMF, degas the mixture three times by freeze-thaw, and polymerize at room temperature for 1-2 hours under nitrogen protection. Then, add deoxygenated PEGMA to the reaction system using a syringe and continue the polymerization reaction for 2 hours. Remove the heat source and nitrogen, pass the reaction solution through silica gel, and concentrate the filtrate under reduced pressure to obtain the final product.
[0007] Furthermore, the preparation process of the functional carbon dots is as follows: citric acid, chitosan, and L-cysteine are dissolved in deionized water, mixed evenly, and then transferred to a hydrothermal reactor to obtain a carbon dot solution through a hydrothermal reaction. Add silver ammonia solution dropwise to the carbon dot solution while stirring at room temperature, and stir for 30-60 min at room temperature; transfer the reaction solution to a dialysis bag with a molecular weight cutoff of 1000 Da and dialyze in deionized water for 48 h, then freeze-dry to obtain the final product.
[0008] Furthermore, the mass ratio of citric acid, chitosan, and L-cysteine is 1:0.2~0.6:0.1~0.3, and the mass molar ratio of carbon dots to silver is 1g:1.5~2.5 mmol.
[0009] Furthermore, the preparation process of the synergistic agent is as follows: Organomontmorillonite was ultrasonically dispersed in deionized water, and acryloyloxyethyltrimethylammonium chloride (DAC) was slowly added dropwise. After the addition was complete, the mixture was stirred at room temperature for 24 hours, centrifuged, washed three times with water, and the solid was vacuum dried. The solid was redispersed in deionized water, and acrylamide (AM) and 2-acrylamidododecyl sulfonic acid were added. Sodium hydroxide was added to adjust the pH to neutral, and nitrogen gas was introduced to add azo initiator VA-044. Under nitrogen protection, the mixture was reacted at 30°C for 12-24 hours, centrifuged, washed three times with water, and vacuum dried to obtain the final product.
[0010] Furthermore, the mass ratio of the organomontmorillonite, DAC, acrylamide, 2-acrylamidododecylsulfonic acid, and VA-044 is 10:30:40~50:40~50:0.1.
[0011] The second objective of this invention is to provide a method for preparing the aqueous wetting and dispersing agent as described above. The method involves ultrasonically dispersing an synergist in deionized water to form a stable and uniform dispersion. Functional carbon dots are then ultrasonically dispersed in deionized water and added dropwise to the uniform dispersion while stirring at a low speed for 1 hour. Subsequently, a star-shaped polymer is dissolved in deionized water and slowly added dropwise to the uniform dispersion, with stirring continued for 2 hours. The mixture is then sieved through a 200-mesh screen to obtain the final product.
[0012] The beneficial effects of this invention are as follows: The aqueous wetting and dispersing agent provided by this invention is composed of a star polymer, functional carbon dots, and a synergist, integrating dispersion, wetting, and antibacterial properties. The star polymer is the main material, and its multi-arm branched topology provides more anchoring points and hydrophilic arms, achieving efficient dispersion and rapid wetting of pigments and fillers. The functional carbon dots contain chitosan and are deposited with silver nanoparticles to provide continuous contact antibacterial properties. The carbon dots themselves generate singlet oxygen under light to achieve photodynamic antibacterial effects, with an antibacterial rate of up to 95% under light. The synergist is montmorillonite modified with organic polymer-linked superlayers. Its layered structure and polymer chains can effectively load carbon dots and trap star polymers, thereby achieving a strong bond in the composite material. Furthermore, it is rich in zwitterions and can form electrostatic attraction with the carboxyl groups and phosphate groups of the star polymer and hydrogen bonding with the carbon dots, thereby enhancing the stability of the composite structure. Attached Figure Description
[0013] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0014] Figure 1 The graph shows the particle size D50 results of each embodiment and comparative example in the dispersibility test.
[0015] Figure 2 The graph shows the surface tension results of each embodiment and comparative example in the wetting performance test.
[0016] Figure 3 The graph shows the antibacterial rate results of each embodiment and comparative example in the antibacterial test. Detailed Implementation
[0017] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0018] Furthermore, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0019] Example: An aqueous wetting and dispersing agent 2-8 parts of synergistic additives were ultrasonically dispersed in a portion of deionized water to form a stable and uniform dispersion. 1-5 parts of functional carbon dots were ultrasonically dispersed in 10 portions of deionized water and then added dropwise to the uniform dispersion while stirring at a low speed for 1 hour. Then, 25-40 parts of star polymer were dissolved and diluted in a portion of deionized water and slowly added dropwise to the uniform dispersion while stirring for another 2 hours. The mixture was then sieved through a 200-mesh screen to obtain a final solid content of 40 wt%.
[0020] The preparation process of the star-shaped polymer is as follows: S1-1. Dissolve dipentaerythritol and triethylamine in dichloromethane, place in an ice-water bath, and slowly add a dichloromethane solution of α-bromoisobutyryl bromide while stirring. After the addition is complete, remove the ice bath and stir at room temperature for 24-48 h. Filter, wash the filtrate successively with dilute hydrochloric acid (HCl), saturated NaHCO3, and saturated brine, dry with anhydrous MgSO4, filter again, evaporate to dryness, and recrystallize from ethyl acetate / n-hexane to obtain a white solid, which is the six-armed initiator. S1-2. Add a six-arm initiator, NaBr, Mesohemin-(MPEG)2 (iron porphyrin catalyst), and monomers MAA (methacrylic acid) and HEMAP (hydroxyethyl methacrylate phosphate) to a dry reaction flask. Add water and DMF, and degas the mixture three times by freeze-thaw. Under nitrogen protection, polymerize at room temperature for 1-2 hours. Then, add deoxygenated PEGMA to the reaction system using a syringe and continue the polymerization reaction for 2 hours. Remove the heat source and nitrogen, and pass the reaction solution through silica gel. Concentrate the filtrate under reduced pressure to obtain the final product.
[0021] The preparation process of the functional carbon dots is as follows: S2-1. Citric acid, chitosan, and L-cysteine are dissolved in deionized water at a mass ratio of 1:0.2~0.6:0.1~0.3. After mixing evenly, the mixture is transferred to a hydrothermal reactor to obtain a carbon dot solution through hydrothermal reaction. S2-2. Under stirring at room temperature, add silver ammonia solution dropwise to the carbon dot solution and stir at room temperature for 30-60 min; filter, dialyze, and dry to obtain functional carbon dots.
[0022] The preparation process of the synergistic agent is as follows: Ten parts of organomontmorillonite were ultrasonically dispersed in deionized water. 30 parts of DAC were slowly added dropwise. After the addition was complete, the mixture was stirred at room temperature for 24 hours. The mixture was then centrifuged, washed three times with water, and the solid was vacuum dried. The solid was redispersed in deionized water, and 40-50 parts of AM and 40-50 parts of 2-acrylamidododecyl sulfonic acid were added. Sodium hydroxide was added to adjust the pH to neutral. Nitrogen gas was introduced, and 0.1 parts of azo initiator VA-044 were added. The mixture was reacted at 30°C for 12-24 hours under nitrogen protection. The mixture was then centrifuged, washed three times with water, and vacuum dried to obtain the final product.
[0023] The main sources of raw materials in the embodiments of this invention are as follows: Example 1: An aqueous wetting and dispersing agent Two parts of synergistic agent were ultrasonically dispersed in 10 parts of deionized water to form a stable and homogeneous dispersion. One part of functional carbon dots was ultrasonically dispersed in 10 parts of deionized water and then added dropwise to the homogeneous dispersion while stirring at a low speed for 1 hour. Then, 37 parts of star polymer were dissolved and diluted in 40 parts of deionized water and slowly added dropwise to the homogeneous dispersion while stirring for another 2 hours. The mixture was then sieved through a 200-mesh screen to obtain a final solid content of 40 wt%.
[0024] The preparation process of the star-shaped polymer is as follows: S1-1. Dissolve 10 mmol of dipentaerythritol and 16 mL of triethylamine in 100 mL of dichloromethane. Place the solution in an ice-water bath and slowly add a dichloromethane solution containing 60 mmol of α-bromoisobutyryl bromide while stirring. After the addition is complete, remove the ice bath and stir at room temperature for 48 h. Filter the solution and wash the filtrate successively with dilute hydrochloric acid (HCl), saturated NaHCO3, and saturated brine. Dry the solution with anhydrous MgSO4, filter again, and evaporate to dryness. Recrystallize the solution from ethyl acetate / n-hexane to obtain a white solid, which is the six-armed initiator with a yield of 67%. ¹H NMR (400 MHz, CDCl3) δ (ppm): 4.28–4.18 (m, 12H, –OCH2–), 3.67 (s, 4H, –CH2–), 1.93 (s, 36H, –C(CH3)2Br).
[0025] S1-2. Add 0.5 mmol of six-arm initiator, 0.5 mol of NaBr, 0.1 mmol of Mesohemin-(MPEG)2, and monomers 50 mmol of MAA and 25 mmol of HEMAP to a dry reaction flask. Perform freeze-thaw degassing three times. Under nitrogen protection, polymerize at room temperature for 1-2 h. Then, add 15 mmol of deoxygenated PEGMA1000 to the reaction system using a syringe and continue the polymerization reaction for 2 h. Remove the heat source and nitrogen. Pass the reaction solution through silica gel, and concentrate the filtrate under reduced pressure to obtain (Mn = 14300 g / mol, PDI = 1.24). (Ref.) ACS Macro Letters ,2018, 7(1), 26-30 (deformation of polymerization conditions) The preparation process of the functional carbon dots is as follows: S2-1. Dissolve 10g citric acid, 3g chitosan, and 2g L-cysteine in 100mL deionized water, mix well, and transfer to a hydrothermal reactor. React at 180℃ for 12 h, then cool, centrifuge, collect the supernatant, filter through a 0.22 μm microporous membrane, and dilute to 2 g / L to obtain a carbon dot solution. S2-2. Under stirring at room temperature, add 1 mL of 0.1 mol / L silver ammonia solution to 25 mL of carbon dot solution and stir for 60 min at room temperature. Transfer the reaction solution to a dialysis bag with a molecular weight cutoff of 1000 Da and dialyze in deionized water for 48 h (changing the water every 8 h). Freeze-dry to obtain functionalized carbon dots (store away from light).
[0026] The preparation process of the synergistic agent is as follows: Ten parts of organomontmorillonite were ultrasonically dispersed in 300 mL of deionized water at a power of 300 W for 30 min. 30 parts of DAC were slowly added dropwise while stirring. After addition, the mixture was stirred at room temperature for 24 h, centrifuged, washed three times with water, and the solid was vacuum dried. The solid was redispersed in deionized water, and 40 parts of AM and 45 parts of 2-acrylamidododecyl sulfonic acid were added. Sodium hydroxide was added to adjust the pH to neutral. Nitrogen gas was introduced, and 0.1 parts of azo initiator VA-044 were added. Under nitrogen protection, the mixture was reacted at 30 °C for 12–24 h, centrifuged, washed three times with water, and vacuum dried to obtain the final product.
[0027] Example 2: An aqueous wetting and dispersing agent Synergistic additives, functional carbon dots, and star polymers prepared using Example 1 Five parts of synergistic additives were ultrasonically dispersed in 15 parts of deionized water to form a stable and homogeneous dispersion. Three parts of functional carbon dots were ultrasonically dispersed in 10 parts of deionized water and then added dropwise to the homogeneous dispersion while stirring at a low speed for 1 hour. Then, 32 parts of star polymer were dissolved and diluted in 35 parts of deionized water and slowly added dropwise to the homogeneous dispersion while stirring for another 2 hours. The mixture was then sieved through a 200-mesh screen to obtain a final solid content of 40 wt%.
[0028] Example 3: An aqueous wetting and dispersing agent Synergistic additives, functional carbon dots, and star polymers prepared using Example 1 Eight parts of synergistic additives were ultrasonically dispersed in 20 parts of deionized water to form a stable and homogeneous dispersion. Five parts of functional carbon dots were ultrasonically dispersed in 10 parts of deionized water and then added dropwise to the homogeneous dispersion while stirring at a low speed for 1 hour. Then, 27 parts of star polymer were dissolved and diluted in 30 parts of deionized water and slowly added dropwise to the homogeneous dispersion while stirring for another 2 hours. The mixture was then sieved through a 200-mesh screen to obtain a final solid content of 40 wt%.
[0029] Example 4: The difference from Example 3 is that in the star polymer synthesis, the molar ratio of the six-arm initiator, MAA, HEMAP, and PEGMA is 1:80:30:25, and the molecular weight of PEGMA is 500.
[0030] Example 5: The difference from Example 3 is that the preparation process of the functional carbon dots is as follows: S2-1. Dissolve 10g citric acid, 4g chitosan, and 2.5g L-cysteine in 100mL deionized water, mix well, and transfer to a hydrothermal reactor. React at 180℃ for 12h, then cool, centrifuge, collect the supernatant, filter through a 0.22μm microporous membrane, and dilute to 2g / L to obtain a carbon dot solution. S2-2. Under stirring at room temperature, add 1.5 mL of 0.1 mol / L silver ammonia solution dropwise to 25 mL of carbon dot solution and stir for 60 min at room temperature. Transfer the reaction solution to a dialysis bag with a molecular weight cutoff of 1000 Da and dialyze in deionized water for 48 h (changing the water every 8 h). Freeze-dry to obtain functionalized carbon dots (store away from light).
[0031] Comparative Example 1: The difference from Example 3 is that the preparation process of the functional carbon dots is as follows: Dissolve 10g citric acid, 3g chitosan, and 2g L-cysteine in 100mL of deionized water, mix well, and transfer to a hydrothermal reactor. React at 180 ℃ for 12 h, then cool, centrifuge, collect the supernatant, filter through a 0.22 μm microporous membrane, dialyze, and freeze-dry to obtain the final product.
[0032] Comparative Example 2: The difference from Example 3 is that the synergist is a solid after DAC intercalation only.
[0033] Comparative Example 3: The difference from Example 3 is that no functional carbon dots were added, and the amount of star polymer was adjusted to 32 parts.
[0034] Comparative Example 4: The difference from Example 3 is that no synergistic agent was added, and the amount of star polymer was adjusted to 35 parts.
[0035] Performance testing: Titanium dioxide (R996) was used as a pigment and filler, and dispersants from the examples and comparative examples were added respectively. Test formulation: 30 g titanium dioxide, 1.5 g dispersant (based on solids), 70 g deionized water, dispersed at high speed for 30 min.
[0036] 1. Storage stability: The prepared dispersible pigment and filler stock solution was sealed in a glass bottle and stored at room temperature (25℃) and 50℃ in a constant temperature incubator for 30 days respectively. The presence of layering, precipitation, discoloration and other phenomena was observed, and the centrifugal stability (1000rpm, 10min) was tested.
[0037] 2. Dispersion performance: The initial particle size (D50) was measured using a laser particle size analyzer. After the slurry was left to stand in a 50℃ constant temperature chamber for 30 days, the particle size was measured again. The particle size growth rate ΔD50 was calculated as (particle size after standing - initial particle size) / initial particle size × 100%. The results are recorded in Table 1.
[0038] Table 1 As can be seen from the data in Table 1, the synergist plays a decisive role in storage stability. After the organomontmorillonite is superlayered with quaternary ammonium salt, the interlayer spacing is increased. The polymerizable quaternary ammonium salt is polymerized with zwitterionic 2-acrylamidododecyl sulfonic acid. AM plays a role in comprehensively increasing the steric hindrance due to its charge properties. The lamellar structure is conducive to the adhesion of carbon dots. The electrostatic attraction between the organic polymer chain and the star polymer makes the prepared dispersant stable and suitable for dispersing pigments and fillers. The long polymer chains grafted with montmorillonite can increase the steric hindrance of the system and work together with the abundant anchoring groups on the star polymer to stabilize the pigments and fillers. The initial particle size is about 250 nm. Figure 1 The particle size growth rate after 30 days of storage is less than 7.5%.
[0039] 3. Wetting properties: The dispersants prepared in the examples and comparative examples were formulated into 0.5 wt% solutions. Static and dynamic surface tensions at 25°C were tested using a static surface tension meter and a dynamic surface tension meter, respectively. The results are as follows: Figure 2As shown. The dynamic surface tension of Examples 1-5 is around 35 mM / m. When montmorillonite without synergists or with only intercalation modification is used as a synergist, the stability of the dispersant is poor, and the wetting performance is also affected. Functional carbon dots can also act as interfacial activity modifiers between synergists and star polymers. When this component is lacking and the amount of star polymer is increased, the interfacial adsorption between the synergist and the synergist is weakened, increasing the surface tension (Comparative Example 3).
[0040] 4. Antibacterial Properties: Referring to GB / T 21866-2008, using *Escherichia coli* (ATCC 25922) as the test strain, a dispersant of 2 wt% was added to a water-based acrylic coating, coated onto a glass plate to form a film (10 cm × 10 cm), and bacterial solution was added and shaken for contact. The film was then incubated for 24 hours under both light and dark conditions, and the antibacterial rate (%) was calculated. Figure 3 As shown, the antibacterial rate of Examples 1-5 can reach over 95% under both light and dark conditions. Under light conditions, the carbon dots can rapidly generate active oxygen, achieving rapid antibacterial action. The antibacterial rate under dark conditions mainly relies on corrosion inhibition and contact sterilization mechanisms. Firstly, silver nanoparticles are deposited on the surface of the carbon dots, which slowly oxidize and release Ag. + The modified montmorillonite contains positively charged quaternary ammonium salts that electrostatically adsorb onto negatively charged cell membranes, disrupting the membrane structure and thus exerting an antibacterial effect. This is evident in the reduced antibacterial rates under both light and dark conditions in Comparative Example 2, although the antibacterial rate decreased under both light and dark conditions. However, the antibacterial rate under dark conditions showed a smaller change compared to that under light conditions, indicating that the dispersant in this application can provide long-lasting antibacterial protection.
[0041] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and illustrations shown and described herein.
Claims
1. An aqueous wetting and dispersing agent, characterized in that, By weight, it comprises: 25-40 parts star-shaped polymer, 1-5 parts functional carbon dots, 2-8 parts synergistic agents, and 60 parts deionized water; wherein... The star-shaped polymer was prepared by polymerizing a six-arm initiator using dipentaerythritol as the initiator and MAA, HEMAP, and PEGMA as comonomers under ATRP initiation conditions; the process is as follows: S1. Dissolve dipentaerythritol and triethylamine in dichloromethane, place in an ice-water bath, and slowly add a dichloromethane solution of α-bromoisobutyryl bromide while stirring. After the addition is complete, remove the ice bath and stir at room temperature for 24-48 h. Filter, wash the filtrate successively with dilute hydrochloric acid (HCl), saturated NaHCO3, and saturated brine, dry with anhydrous MgSO4, filter again, evaporate to dryness, and recrystallize from ethyl acetate / n-hexane to obtain a white solid, which is the six-armed initiator. S2. Add the six-arm initiator, NaBr, Mesohemin-(MPEG)2, and monomers MAA and HEMAP to a dry reaction flask. Add water and DMF, degas the mixture three times by freeze-thaw, and polymerize at room temperature for 1-2 hours under nitrogen protection. Then, add deoxygenated PEGMA to the reaction system using a syringe and continue the polymerization reaction for 2 hours. Remove the heat source and nitrogen, pass the reaction solution through silica gel, and concentrate the filtrate under reduced pressure to obtain the final product. The functional carbon dots are prepared by hydrothermal reaction of citric acid, chitosan, and L-cysteine, followed by the deposition of silver ions on the surface of the carbon dots by reducing silver ammonia. The preparation process is as follows: Citric acid, chitosan, and L-cysteine are dissolved in deionized water, mixed evenly, and then transferred to a hydrothermal reactor to obtain a carbon dot solution through hydrothermal reaction. Silver ammonia solution was added dropwise to the carbon dot solution with stirring at room temperature for 30-60 min; the reaction solution was then transferred to a dialysis bag with a molecular weight cutoff of 1000 Da and dialyzed in deionized water for 48 h, followed by freeze drying to obtain the final product. The synergistic agent is modified montmorillonite, which is prepared by intercalation modification of organomontmorillonite with acryloyloxyethyltrimethylammonium chloride followed by polymerization reaction with acrylamide and 2-acrylamidododecyl sulfonic acid; the preparation process is as follows: Organomontmorillonite was ultrasonically dispersed in deionized water, and acryloyloxyethyltrimethylammonium chloride was slowly added dropwise. After the addition was complete, the mixture was stirred at room temperature for 24 hours, centrifuged, washed three times with water, and the solid was dried under vacuum. The solid was redispersed in deionized water, and acrylamide, 2-acrylamidododecylsulfonic acid, and azo initiator VA-044 were added. The mixture was reacted at 30°C for 12-24 hours under nitrogen protection, centrifuged, washed three times with water, and dried under vacuum to obtain the final product. The mass ratio of citric acid, chitosan, and L-cysteine is 1:0.2~0.6:0.1~0.3, and the mass molar ratio of carbon dots to silver is 1g:1.5~2.5 mmol. The mass ratio of the organomontmorillonite, acryloyloxyethyltrimethylammonium chloride, acrylamide, 2-acrylamidododecylsulfonic acid, and VA-044 is 10:30:40~50:40~50:0.
1.
2. A method for preparing the aqueous wetting and dispersing agent as described in claim 1, characterized in that, The synergistic agent was ultrasonically dispersed in deionized water to form a stable and uniform dispersion. The functional carbon dots were ultrasonically dispersed in deionized water and then added dropwise to the uniform dispersion while stirring at a low speed for 1 hour. Then, the star polymer was dissolved in deionized water and slowly added dropwise to the uniform dispersion while stirring for another 2 hours. The mixture was then sieved through a 200-mesh screen to obtain the final product.
Citation Information
Patent Citations
pH-responsive 6-arm star block copolymer and preparation method and application thereof
CN102702453A
Biomass-based high-efficiency sulfur-nitrogen-doped carbon quantum dots and preparation method and application thereof
CN109385274A